Analysis of Moral Values in The Standards of the Ministry of National Education Perspective in the Process of Teaching the Arabic Language in Indonesia | Tahlīl Al-Qiyam Al-Akhlāqīyah ‘Ala Dhou - Nurlaila Nurlaila; Muassomah Muassomah; Munirul Abidin (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
This research is motivated by the demoralization of most of the students who still behave badly due suboptimal character education. This research describes and analyzes the character values according to the Ministry of National Education which are instilled in students in the process of Arabic learning, and the inhibiting and supporting factors for the application of these character values. The study uses a qualitative approach with descriptive method. The results showed that the application of character values in the process of Arabic learning is included in the planning, implementation, and assessment. The teacher integrated character education in the process of Arabic learning by using various approaches, methods, and strategies. Character values that are applied in the process of Arabic learning consist of 21 values. Integrating character values in the process of Arabic learning is inseparable from the inhibiting factors and supporting factors which include nurture and nature factors. Thus, Arabic teachers always try to instill character values to students effectively so that students not only understand the subject matter but also gain positive characters. This research suggests follow-up research studies by comparing two or more educational institutions.